Astragalus Polysaccharides Ameliorate Diet-Induced Gallstone Formation by Modulating Synthesis of Bile Acids and the Gut Microbiota - Zhuang, Qian; Ye, Xin; Shen, Shuang; Cheng, Jinnian; Shi, Yan; Wu, Shan; Xia, Jie; Ning, Min; Dong, Zhixia; Wan, Xinjian (Frontiers in Pharmacology, 2021)
Cholesterol gallstone (CG) disease has relationships with several metabolic abnormalities. Astragalus polysaccharides (APS) have been shown to have multiple benefits against metabolic disorders. We attempted to uncover the effect and mechanism of action of APS on diet-induced CG formation in mice. Animals were fed a chow diet or lithogenic diet (LD) with or without APS supplementation. The effect of APS on CG formation was evaluated. The level of individual bile acids (BAs) in gallbladder bile and ileum were measured by liquid chromatography-tandem mass spectrometry. Real-time reverse transcription-quantitative polymerase chain reaction and western blotting were used to assess expression of the genes involved in BA metabolism and the enterohepatic circulation. Cecal contents were collected to characterize microbiota profiles. APS ameliorated LD-induced CG formation in mice. APS reduced the level of total cholesterol, bile acid hydrophobicity index and cholesterol saturation index in gallbladder bile. The protective effect of APS might result from reduced absorption of cholic acid in the intestine and increased hepatic BA synthesis. APS relieved the LD-induced activation of the intestinal farnesoid X receptor and decreased ileal expression of fibroblast growth factor 15. In the liver, expression of cytochrome P450 (Cyp) enzyme Cyp7a1 and Cyp7b1 was increased, whereas expression of adenosine triphosphate-binding cassette (Abc) transporters Abcg5 and Abcg8 was decreased by APS. APS improved the diversity of the gut microbiota and increased the relative abundance of the Bacteroidetes phylum. APS had demonstratable benefits against CG disease, which might be associated with enhanced BA synthesis and improved gut microbiota. Our results suggest that APS may be a potential strategy for the prevention of CG disease.